(untitled) (Comillas Journal of International Relations, 2014)
International development co-operation has always been a cornerstone of Spanish foreign policy. Not only has it been an expression of solidarity contributing to the development of countries and peoples, it has also bolstered foreign relations and, by reflecting the plurality of actors involved in International Cooperation, it has further affirmed Spain’s position in favour of multilateralism. Given the scenario of the present economic crisis there has been a noticeable drop in Spanish foreign aid, whose consequence has been a loss of influence in the Government’s and other Institution’s external actions, weakening Spain’s role in the world.